Pengaruh Mutu Pelayanan Dan Prosedur Pelayanan Terhadap Kepuasan Masyarakat (Studi Penerbitan Rekomendasi Peruntukan Ruang Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Tulungagung) - Dian Aviana (Universitas Islam Kadiri, 2020)
Good public services are services that are able to provide satisfaction to the community. Become the basic actualization and existence of bureaucracy which is reflected in attitudes and behavior in providing services to the community. This research uses quantitative research methods with a population of 60 communities as respondents. This study aims: (1) Analyzing the effect service quality and service procedures on community satisfaction in carrying out service issuance of recommendations for the use of space. (2) Analyzing the effect of service quality on community satisfaction in carrying out the service of issuing recommendations for the use of space. (3) Analyzing the effect of service procedures on community satisfaction in performing services issuing recommendations for the use of space. The research variables consist of dependent variable is community satisfaction and the independent variables, namely service quality and service procedures. The analysis used is data in the form of numbers. Whereas technical data analysis uses: (1) descriptive statistics, (2) inferential statistics, and (3) multiple linear regression tests. The results showed that: (1) The effect of service quality and service procedures had a significant effect on community satisfaction in carrying out service issuance of space utilization recommendations. (2) The effect of service quality has a significant influence on community satisfaction in carrying out the service of issuing recommendations for the use of space. (3) The effect of service procedures has a significant effect on community satisfaction in performing the service of issuing recommendations for the use of space. (4) Service Quality Variables have the most dominant influence on community satisfaction in carrying out services issuing recommendations for the use of space.